Evaluation of the effect of hydrothermal pretreatment on kitchen and fruit wastes for bacterial cellulose fermentation medium - Muhammad Irhamni Haziqi, Nasharudin; Chua, Gek Kee; Mohd Hairul, Ab. Rahim; Nazira, Mahmud (Springer, 2025)
Purpose: Hydrothermal pretreatment stands out for its efficiency and simplicity yet offers economic and environmental benefits. Its application on non-fibrous organic waste such as kitchen and fruit waste are deemed efficient and does not require extreme working parameters. This study evaluated the effect of predetermined parameters on the hydrothermal pretreatment of various food waste. We aimed to establish a set of parameters for the hydrothermal pretreatment, to promote the utilisation of waste for fermentation into value-added products. Methods: The kitchen and fruit wastes were homogenized and treated at varying temperatures, incubation times, and water ratios. Reducing sugar, protein, and lipid content was analysed pre- and post-treatment. The treated waste was used as a medium for bacterial cellulose fermentation and the yield was compared to chemical medium. Results: The models identified the optimum parameters for maximizing glucose production were at incubation temperature of 115 °C for 75 min and 1:2 waste-to-water ratio, achieving 449.031 mg/mL (kitchen waste), 382.033 mg/mL (guava waste), and 358.840 mg/mL (watermelon waste), with satisfactory desirability and model fit for kitchen waste and guava waste. Attempts to produce bacterial cellulose (BC) from the treated waste recorded promising results. While kitchen waste had higher glucose content post-hydrothermal pretreatment, guava waste and watermelon waste produced more BC due to lower oil content, which did not interfere with the oxygen transfer. Conclusion: The conducted hydrothermal pretreatment at the pre-optimized conditions increased the potential of the food waste tested as a media substitute for BC production.